Study of the correlation between platelet parameters in the patients with coronary heart disease - Abdinur, Mohamed Abdirahman; Yong, Xie; Lingcai, Kong; Mohamud, Farah Abdidahir; Mohamud, Jamac Abdidahir; Isse, Abdinasir Sharif (International Journal of Research in Medical Sciences, 2017)
Background: The incidence and development of coronary heart disease are ultimately associated with the size and function of platelet. Present study aimed to determine the clinical value of platelet distribution width as an indicator for prediction or risk stratification of coronary heart disease by retrospective analysis of particular population. Methods: This retrospective study covered a total of 150 patients that were included due to a variety of indications for coronary angiography. The control group N-CHD was the patients without coronary heart disease confirmed by coronary angiography examination. The S-CHD group was patients with Stable type coronary heart disease confirmed diagnosis by coronary angiography examination. Study group 2 defined as group ACS were the patients who suffering acute coronary syndrome episode at admission and received coronary angiography and interventional treatment thereafter. Results: The PDW of S-CHD and ACS were 13.85±2.68 and 13.89±1.16, respectively, and there was no significant difference, while the PDW of the N-CHD group was 12.58±2.11, and the values of the first two groups were significantly higher than those of the N-CHD group. In addition, the MPV and P-LCR of S-CHD were significantly higher than those of N-CHD group (11.14±1.17 versus 10.51±0.91 and 32.71±9.99 versus 28.41±7.69), respectively P<0.01; but there was no significant difference between S-CHD and ACS. Conclusions: PDW, MPV, and P-LCR are the platelet volume indicators that can reflex the variability of circulation platelets; their increase was highly and positively associated with Coronary heart disease.